Strategy of Implementing the Canvas Business Model Using SWOT Analysis in Developing the Tour & Travel Business of Umrah and Hajj Tourism at PT. Sa'yan Masykuro - Henisyafitri, Berliana; Nirawati, Lia (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The development of the Hajj and Umrah travel business creates selective competition. PT. Sa'yan Masykuro is one of the companies engaged in Hajj and Umrah Services or known as PPIH (Hajj Travel Organizer). This study aims to analyze the Sa'yan Masykuro model using the business model canvas approach and evaluate it based on SWOT analysis to produce recommendations for improving the elements of the business model block. This study uses a qualitative descriptive approach using Business Model Canvas (BMC) data analysis techniques and SWOT analysis which includes the use of IFAS and EFAS. The data collection method was interviews with several selected informants and document research. The informants of this study consisted of randomly selected owners, employees, and customers of Sa'yan Masykuro, totaling 11 people who had made repeated purchases. The findings show that the SWOT analysis diagram leads to a diversification strategy (product/market) that is an input for the improvement of the canvas model business. From its implementation, it is recommended to improve the nine elements of the Business Model Canvas, as well as strategies that allow the development of the Umrah & Hajj Tour & Hajj Tourism Business of PT. That is a very serious matter.